Metformin Attenuates the Metabolic Disturbance and Depression-like Behaviors Induced by Corticosterone and Mediates the Glucose Metabolism Pathway - Hao, Yong; Tong, Yingpeng; Guo, Yanhong; Lang, Xiaoe; Huang, Xinxin; Xie, Xiaoxian; Guan, Yangtai; Li, Zezhi (Pharmacopsychiatry, 2021)
Background Metabolism disturbances are common in patients with depression. The drug metformin has been reported to exhibit antidepressant activity. The purpose of this study was to investigate metabolism disturbances induced by corticosterone (CORT) and determine if metformin can reverse these effects and their accompanying depression-like behaviors.Methods Rats were exposed to corticosterone with or without metformin administration. Depression-like behaviors were tested. Gene expression was confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot analysis. In addition, the metabolites were quantified by LC-MS/MS analysis.Results Metformin attenuated the depression-like behaviors induced by CORT. Furthermore, metformin reversed disturbances in body weight, serum glucose, and triglyceride levels, as well as hepatic TG levels induced by CORT. Metformin normalized the alterations in the expression of glucose metabolism-related genes (PGC-1α, G6pc, Pepck, Gck, PYGL, Gys2, PKLR, GLUT4) and insulin resistance-related genes (AdipoR1, AdipoR2) in the muscles and livers of rats induced by CORT. Metabolomic analysis showed that metformin reversed the effects of CORT on 11 metabolites involved in the pathways of the tricarboxylic acid cycle, glycolysis, and gluconeogenesis (3-phospho-D-glycerate, β-D-fructose 6-phosphate, D-glucose 6-phosphate, and pyruvate).Conclusion Our findings suggest that metformin can attenuate metabolism disturbances and depression-like behaviors induced by CORT mediating the glucose metabolism pathway.
Keywords: metformin; glucose metabolism; LC-MS/MS; depression-like behavior; metabolomics analysis